A lithium-supplementing electrode and battery with coordinated positive and negative electrodes

By adopting the efficient lithium supplement technology of positive and negative electrode synergistically in lithium iron phosphate batteries, and using graphite and Mo-W@BNC-supported composites for lithium supplementation, the problem of lithium loss in the battery during service is solved, and efficient lithium compensation and battery life are achieved.

CN119069642BActive Publication Date: 2025-03-28HUAZHONG UNIV OF SCI & TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411549929.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-28
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing lithium iron phosphate batteries have severe lithium loss during service, resulting in short life. The existing lithium supplement technology only targets the initial lithium loss and fails to effectively solve the problem of lithium loss during service.

Method used

The high-efficiency lithium supplement technology is adopted that synergizes positive and negative electrodes. The negative electrode uses graphite prelithiation with biphenyl lithium, and the positive electrode uses the lithium oxalate/lithium square compound supported by Mo-W@BNC as the lithium supplement layer. By regulating the activity of the lithium supplement material, effective compensation for lithium loss is achieved.

Benefits of technology

The first Coulomb efficiency of the simulated battery reached 99%, and the capacity retention rate of 5,000 cycles reached more than 94%, significantly extending the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069642B_ABST
    Figure CN119069642B_ABST
Patent Text Reader

Abstract

The present invention provides a lithium replenishing electrode and a battery with coordinated positive and negative electrodes. The negative lithium replenishing electrode is a lithium electrode rich in inorganic matter after graphite is pre-lithiated with biphenyl lithium and then treated with fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene, and the mass ratio of fluoroethylene carbonate to ethoxy (pentafluoro) cyclotriphosphazene is 5-3:2-1; the positive lithium replenishing electrode includes a positive electrode layer and a lithium replenishing layer coated on the positive electrode layer, the positive electrode layer is a lithium iron phosphate positive electrode layer, and the lithium replenishing layer is a lithium oxalate and lithium squarate composite supported by Mo-W@BNC; wherein the mass ratio of the lithium replenishing layer to the positive electrode layer is 0.5-2:15-20, and the mass ratio of Mo-W@BNC to lithium oxalate and lithium squarate is 0.5-2:5-10. This electrode targets lithium loss before and during battery service by regulating the activity of lithium replenishment materials and adopting efficient lithium replenishment technology that cooperates with positive and negative electrodes. It breaks through the shackles of existing battery material systems and structures, and is of great significance for the development of high-performance batteries suitable for large-scale energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium-supplementing electrode and a battery with coordinated positive and negative electrodes. Background Art

[0002] Lithium-ion energy storage has fast response, flexible configuration and short construction period, and is a new energy storage technology that countries around the world are competing to develop. Lithium batteries came out in 1990 and were first used in watt-level electronic products, and then promoted to electric vehicles, with a scale of kilowatts; but large-scale lithium-ion energy storage power stations in the power system reach hundreds of megawatts, which is magnified tens of thousands of times. The frequency of charging and discharging is much higher than that of electric vehicles, and the life requirements are extremely strict. The most widely used lithium iron phosphate energy storage battery uses the material system and structural design of power batteries, but has the problem of short life (cycle life of 5,000 times and service life of 8 years), which is still far from the requirements of power energy storage.

[0003] One of the key technical bottlenecks in improving the life of lithium iron phosphate batteries is that there is a lot of lithium loss during the first charge and service, which is mainly caused by factors such as SEI formation and rupture regrowth. Therefore, compensating for the loss of active lithium in the battery system is the key to fully improving the battery life. The use of pre-lithiation technology that can provide additional active lithium to replenish lithium is considered to be the most effective and promising technical means at this stage. After development, the pre-lithiation materials that have been developed include stable lithium metal powder (CN102642024A; CN114899408B, etc.), organic lithium reagents (CN114221022A; CN112038583A, etc.), conversion reaction positive electrode additives (CN112542589B), traditional lithium-rich positive electrode additives (CN110518297A; CN115954453A), etc. However, these technologies are only for one-time lithium replenishment, only for the loss of active lithium in the early stage of the battery, and there is no effective solution strategy for the lithium loss in the battery service. Summary of the invention

[0004] In view of the technical problems existing in the prior art, the present invention provides a lithium-supplementing electrode and battery with coordinated positive and negative electrodes. The first coulombic efficiency of a simulated battery containing the electrode can reach 99%, and the capacity retention rate after 5,000 cycles can still reach more than 94%.

[0005] The present invention adopts the following technical scheme: a positive and negative electrode synergistic lithium replenishing electrode, the negative electrode lithium replenishing electrode is a lithium electrode rich in inorganic matter after graphite is pre-lithiated with biphenyl lithium and then treated with fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene, the concentration of biphenyl lithium is 1M, the solvent is tetrahydrofuran, the pre-lithiation time is 5-20 minutes, and the mass ratio of fluoroethylene carbonate and ethoxy (pentafluoro) cyclotriphosphazene is 5-3:2-1;

[0006] The positive lithium replenishing electrode comprises a positive electrode layer and a lithium replenishing layer coated on the positive electrode layer, wherein the positive electrode layer is a lithium iron phosphate positive electrode layer, and the lithium replenishing layer is a lithium oxalate / lithium squarate composite supported by Mo-W@BNC; wherein the mass ratio of the lithium replenishing layer to the positive electrode layer is 0.5~2:15~20, and the mass ratio of Mo-W@BNC to lithium oxalate and lithium squarate is 0.5~2:5~10.

[0007] The present invention also aims to protect a battery comprising the above-mentioned positive and negative coordinated lithium-supplementing electrode.

[0008] Compared with the prior art, the beneficial effects of the present invention are as follows: the positive and negative coordinated lithium replenishing electrodes and batteries provided by the present invention target the lithium loss of the battery before and during service by regulating the activity of the lithium replenishing material and adopting the positive and negative coordinated efficient lithium replenishing technology, so that the first coulombic efficiency of the simulated battery can reach 99%, and the capacity retention rate after 5000 cycles can still reach more than 94%, breaking through the shackles of the existing battery material system and structure, and is of great significance for the development of high-performance batteries suitable for large-scale energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 : XRD diagrams of Gr and p-Gr electrodes before and after lithiation in Example 1 of the present invention;

[0010] Figure 2 This is a comparison diagram of the initial voltages of the Gr and p-Gr electrodes before and after lithiation in Example 1 of the present invention;

[0011] Figure 3 The first cycle charge-discharge specific capacity diagram of the Gr and p-Gr electrodes before and after lithiation in Example 1 of the present invention;

[0012] Figure 4 is the XRD pattern of Mo-W@BNC prepared in Example 1 of the present invention;

[0013] Figure 5 This is the XRD diagram of the composite lithium supplement Mo-W@BNC-L2-L4 prepared in Example 1 of the present invention;

[0014] Figure 6 This is a SEM electron microscope image of the Mo-W@BNC-L2-L4 material prepared in Example 1 of the present invention;

[0015] Figure 7 This is the first cycle charge and discharge specific capacity diagram of the Mo-W@BNC-L2-L4 electrode prepared in Example 1 of the present invention;

[0016] Figure 8 This is the decomposition potential diagram of the Mo-W@BNC-L2-L4 electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0017] The present invention aims at the lithium loss of the battery before and during service, regulates the activity of the lithium replenishing material, and adopts the efficient lithium replenishing technology of the positive and negative electrodes in coordination, so that the first coulombic efficiency of the simulated battery can reach 99%, and the capacity retention rate after 5000 cycles can still reach more than 94%, breaking through the shackles of the existing battery material system and structure. The specific method is as follows:

[0018] The positive and negative electrodes cooperate to replenish lithium, and the negative electrode replenishing lithium electrode is a lithiated electrode rich in inorganic matter, mainly an electrode after graphite is pre-lithiated with biphenyl lithium and then treated with FEC-PFPN, wherein the concentration of biphenyl lithium is 1 M, the solvent is tetrahydrofuran, the pre-lithiation time is 5-20 min, and the mass ratio of fluoroethylene carbonate (FEC) and ethoxy (pentafluoro) cyclotriphosphazene (PFPN) is 5~3:2~1.

[0019] Specifically, the preparation of the negative lithium supplement electrode can be carried out by the following method: the negative electrode material containing graphite is slurried and evenly coated on a copper foil and dried to obtain an electrode piece, and then the electrode piece is transferred to an inert atmosphere (such as argon, nitrogen, etc.) for protection and immersed in a lithium biphenyl / tetrahydrofuran solution, and then washed with a tetrahydrofuran solvent, and then immersed in a fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene solvent and dried to obtain the electrode piece.

[0020] The positive lithium replenishment electrode mainly includes a positive electrode layer and a lithium replenishment layer, the lower layer is a lithium iron phosphate positive electrode layer, and the upper layer is a lithium oxalate and lithium squarate composite supported by Mo-W@BNC, which is coated on the positive electrode layer. The mass ratio of the lithium replenishment layer to the positive electrode layer is 0.5~2:15~20, and the mass ratio of Mo-W@BNC to lithium oxalate and lithium squarate is 0.5~2:5~10.

[0021] Specifically, the preparation of the positive lithium replenishing electrode can be carried out by the following method: the positive electrode material containing lithium iron phosphate is homogenized and then evenly coated on aluminum foil and dried to obtain a pole piece; Mo-W@BNC is spray-dried with lithium oxalate and lithium squarate lithium replenishing agents to obtain a composite lithium replenishing agent; the material containing the composite lithium replenishing agent is homogenized and evenly coated on the pole piece as a lithium replenishing layer, and dried to obtain a positive lithium replenishing electrode.

[0022] Among them, the mass ratio of lithium oxalate to lithium squarate is 0.5~1:1~2. For example, a ratio of 1:1 can be selected.

[0023] In the preparation of the positive lithium supplement electrode, Mo-W@BNC can be prepared by the following method: ammonium molybdate, ammonium tungstate, C3N4 and boric acid are evenly mixed and placed in a tubular furnace and heated to 800~900℃ and kept warm for 5~8h to obtain the obtained product; wherein, the mass ratio of ammonium molybdate to ammonium tungstate is 5~3:1~0.5, the mass volume ratio of C3N4 to boric acid is 5~3:1~0.5, and the mass of ammonium molybdate, ammonium tungstate and C3N4 is 0.5~1:2~4.

[0024] In the present invention, in the preparation of the negative lithium supplement electrode, the negative electrode material is slurried and coated on the copper foil and then dried at 60-90°C; in the preparation of the positive lithium supplement electrode, the positive electrode material is slurried and coated on the aluminum foil and then dried at 100-120°C.

[0025] In addition, it can be understood by those skilled in the art that the negative electrode material and the positive electrode material also include a conductive agent and a binder. Generally, the content of the conductive agent is 3-5 wt% of the lithium supplement layer material or graphite, and the content of the binder is 3-5 wt% of the lithium supplement layer material or graphite. The conductive agent can be Super P or KB1400, and the binder can be polyvinylidene fluoride, carboxymethyl cellulose or sodium alginate.

[0026] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0027] The following embodiments are only used to illustrate the present invention, but are not limited to the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.

[0028] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0029] Example 1

[0030] This embodiment provides a method for preparing a positive-negative coordinated lithium-supplementing electrode and a battery, which is specifically as follows:

[0031] Preparation of negative lithium replenishment electrode: Graphite, Super P, and carboxymethyl cellulose are slurried in a mass ratio of 8:1:1 and water as solvent, and then evenly coated on copper foil and dried at 80°C in a vacuum for 12 hours to obtain the pole piece Gr. Then, Gr is transferred to an inert atmosphere and soaked in 1M lithium biphenyl / tetrahydrofuran solution for 10 min, then washed with tetrahydrofuran solvent, and then soaked in a 3:2 volume ratio of fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene (i.e., FEC-PFPN) solvent. After drying, the negative lithium replenishment electrode (p-Gr) is obtained. The X-ray diffraction spectra (XRD spectra) of Gr and p-Gr electrodes before and after lithiation are shown in Figure 2. Figure 1 As shown in Figure 2, the carbon peak at 27.3° shifts to the left, and there is a characteristic peak of Li-Gr at 21.5°; Figure 2 As shown in Figure 2, compared with Gr, the initial potential of p-Gr dropped to 0.27 V; Figure 3 As shown, the irreversible active lithium loss of 63 mAh / g was compensated, fully demonstrating the successful pre-lithiation of the graphite anode.

[0032] Preparation of positive lithium supplement electrode: lithium iron phosphate, Super P, polyvinylidene fluoride (PVDF) are slurried in a mass ratio of 8:1:1 with nitrogen-methylpyrrolidone (NMP) as solvent, and then evenly coated on aluminum foil and dried in vacuum at 110°C for 12 hours to obtain the pole piece LFP.

[0033] After ammonium molybdate, ammonium tungstate, C3N4 and boric acid were uniformly mixed (the mass ratio of ammonium molybdate to ammonium tungstate was 5:1, the mass volume ratio of C3N4 to boric acid was 5:1, and the mass ratio of ammonium molybdate, ammonium tungstate and C3N4 was 1:2), the mixture was placed in a tube furnace and heated from 10°C to 800°C for 8h to obtain Mo-W@BNC (its XRD pattern is shown in Figure 4 ), and then Mo-W@BNC and lithium supplement agent (lithium oxalate: lithium squarate = 1:1) were spray dried to prepare composite lithium supplement agent Mo-W@BNC-L2-L4 (its XRD pattern is shown in Figure 5 ).

[0034] Mo-W@BNC-L2-L4, KB1400 and PVDF were slurried in a mass ratio of 8:1:1 and homogenized with nitrogen-methylpyrrolidone NMP as solvent, and then evenly coated on LFP as a lithium replenishing layer (the mass ratio of the lithium replenishing layer to LFP was 1:20). After drying, the positive lithium replenishing electrode Mo-W@BNC-L2-L4-LFP was obtained.

[0035] Preparation of simulated battery: p-Gr was used as the negative electrode of the simulated battery, Mo-W@BNC-L2-L4-LFP was used as the positive electrode, 1 mol of lithium hexafluorophosphate (LiPF6) was dissolved in 1L of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (solvent volume ratio of 3:7), the additive was 5% fluoroethylene carbonate (FEC), and the diaphragm was polypropylene (PP). The positive electrode, negative electrode, electrolyte, and diaphragm were assembled into simulated battery 1 in an argon-protected glove box.

[0036] Example 2

[0037] This embodiment provides a method for preparing a positive-negative coordinated lithium-supplementing electrode and a battery, which is specifically as follows:

[0038] Preparation of negative lithium replenishing electrode: Graphite, Super P and carboxymethyl cellulose were slurried in a mass ratio of 8:1:1 with water as solvent and then evenly coated on copper foil and dried in vacuum at 70°C for 12 hours to obtain the pole piece Gr. Then, Gr was transferred to an inert atmosphere for protection and soaked in 1M lithium biphenyl / tetrahydrofuran solution for 10 min, then washed with tetrahydrofuran solvent, and then soaked in a 4:1 volume ratio of fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene (i.e., FEC-PFPN) solvent, and dried to obtain the negative lithium replenishing electrode (p-Gr).

[0039] Preparation of positive lithium supplement electrode: lithium iron phosphate, Super P, polyvinylidene fluoride (PVDF) are slurried in a mass ratio of 8:1:1 with nitrogen-methylpyrrolidone (NMP) as solvent, and then evenly coated on aluminum foil and dried in vacuum at 110°C for 12 hours to obtain the pole piece LFP.

[0040] After ammonium molybdate, ammonium tungstate, C3N4 and boric acid were uniformly mixed (the mass ratio of ammonium molybdate to ammonium tungstate was 5:1, the mass volume ratio of C3N4 to boric acid was 5:1, and the mass ratio of ammonium molybdate, ammonium tungstate and C3N4 was 1:2), the mixture was placed in a tubular furnace and heated from 10°C to 800°C for 8 hours to obtain Mo-W@BNC. Subsequently, Mo-W@BNC and a lithium supplement (lithium oxalate: lithium squarate = 1:1) were spray-dried to obtain a composite lithium supplement Mo-W@BNC-L2-L4.

[0041] Mo-W@BNC-L2-L4, KB1400 and PVDF were slurried in a mass ratio of 8:1:1 and homogenized with nitrogen-methylpyrrolidone NMP as solvent, and then evenly coated on LFP as a lithium replenishing layer (the mass ratio of the lithium replenishing layer to LFP was 1:20). After drying, the positive lithium replenishing electrode Mo-W@BNC-L2-L4-LFP was obtained.

[0042] Preparation of simulated battery: p-Gr was used as the negative electrode of the simulated battery, Mo-W@BNC-L2-L4-LFP was used as the positive electrode, 1 mol of lithium hexafluorophosphate (LiPF6) was dissolved in 1L of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (solvent volume ratio of 3:7), the additive was 5% fluoroethylene carbonate (FEC), and the diaphragm was polypropylene (PP). The positive electrode, negative electrode, electrolyte, and diaphragm were assembled into simulated battery 2 in an argon-protected glove box.

[0043] Example 3

[0044] This embodiment provides a method for preparing a positive-negative coordinated lithium-supplementing electrode and a battery, which is specifically as follows:

[0045] Preparation of negative lithium replenishing electrode: Graphite, Super P and carboxymethyl cellulose were slurried in a mass ratio of 8:1:1 with water as solvent and then evenly coated on copper foil and dried in vacuum at 70°C for 12 hours to obtain the electrode Gr. Gr was then transferred to an inert atmosphere for protection and soaked in 1M lithium biphenyl / tetrahydrofuran solution for 10 min, then washed with tetrahydrofuran solvent, and then soaked in a fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene (i.e., FEC-PFPN) solvent with a volume ratio of 3:2. After drying, the negative lithium replenishing electrode (p-Gr) was obtained.

[0046] Preparation of positive lithium supplement electrode: lithium iron phosphate, Super P, polyvinylidene fluoride (PVDF) are slurried in a mass ratio of 8:1:1 with nitrogen-methylpyrrolidone (NMP) as solvent, and then evenly coated on aluminum foil and dried in vacuum at 110°C for 12 hours to obtain the pole piece LFP.

[0047] After ammonium molybdate, ammonium tungstate, C3N4 and boric acid were uniformly mixed (the mass ratio of ammonium molybdate to ammonium tungstate was 5:1, the mass volume ratio of C3N4 to boric acid was 5:1, and the mass ratio of ammonium molybdate, ammonium tungstate and C3N4 was 1:2), the mixture was placed in a tubular furnace and heated from 10°C to 800°C for 6 hours to obtain Mo-W@BNC. Subsequently, Mo-W@BNC and a lithium supplement (lithium oxalate: lithium squarate = 1:1) were spray-dried to obtain a composite lithium supplement Mo-W@BNC-L2-L4.

[0048] Mo-W@BNC-L2-L4, KB1400 and PVDF were slurried in a mass ratio of 8:1:1 and homogenized with nitrogen-methylpyrrolidone NMP as solvent, and then evenly coated on LFP as a lithium replenishing layer (the mass ratio of the lithium replenishing layer to LFP was 1:20). After drying, the positive lithium replenishing electrode Mo-W@BNC-L2-L4-LFP was obtained.

[0049] Preparation of simulated battery: p-Gr was used as the negative electrode of the simulated battery, Mo-W@BNC-L2-L4-LFP was used as the positive electrode, the electrolyte was 1 mol of lithium hexafluorophosphate (LiPF6) dissolved in 1L of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (solvent volume ratio of 3:7), the additive was 5% fluoroethylene carbonate (FEC), and the separator was polypropylene (PP). The positive electrode, negative electrode, electrolyte, and separator were assembled into a simulated battery 3 in an argon-protected glove box.

[0050] Example 4

[0051] This embodiment provides a method for preparing a positive-negative coordinated lithium-supplementing electrode and a battery, which is specifically as follows:

[0052] Preparation of negative lithium replenishing electrode: Graphite, Super P and carboxymethyl cellulose were slurried in a mass ratio of 8:1:1 with water as solvent and then evenly coated on copper foil and dried in vacuum at 70°C for 12 hours to obtain the electrode Gr. Gr was then transferred to an inert atmosphere for protection and soaked in 1M lithium biphenyl / tetrahydrofuran solution for 10 min, then washed with tetrahydrofuran solvent, and then soaked in a fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene (i.e., FEC-PFPN) solvent with a volume ratio of 3:2. After drying, the negative lithium replenishing electrode (p-Gr) was obtained.

[0053] Preparation of positive lithium supplement electrode: lithium iron phosphate, Super P, polyvinylidene fluoride (PVDF) are slurried in a mass ratio of 8:1:1 with nitrogen-methylpyrrolidone (NMP) as solvent, and then evenly coated on aluminum foil and dried in vacuum at 110°C for 12 hours to obtain the pole piece LFP.

[0054] After ammonium molybdate, ammonium tungstate, C3N4 and boric acid were uniformly mixed (the mass ratio of ammonium molybdate to ammonium tungstate was 5:1, the mass volume ratio of C3N4 to boric acid was 5:1, and the mass ratio of ammonium molybdate, ammonium tungstate and C3N4 was 1:2), the mixture was placed in a tubular furnace and heated from 10°C to 800°C for 8 hours to obtain Mo-W@BNC. Subsequently, Mo-W@BNC and a lithium supplement (lithium oxalate: lithium squarate = 1:1) were spray-dried to obtain a composite lithium supplement Mo-W@BNC-L2-L4.

[0055] Mo-W@BNC-L2-L4, KB1400 and PVDF were slurried in a mass ratio of 8:1:1 and homogenized with nitrogen-methylpyrrolidone NMP as solvent, and then evenly coated on LFP as a lithium replenishing layer (the mass ratio of the lithium replenishing layer to LFP was 1:10). After drying, the positive lithium replenishing electrode Mo-W@BNC-L2-L4-LFP was obtained.

[0056] Preparation of simulated battery: p-Gr was used as the negative electrode of the simulated battery, Mo-W@BNC-L2-L4-LFP was used as the positive electrode, the electrolyte was 1 mol of lithium hexafluorophosphate (LiPF6) dissolved in 1L of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (solvent volume ratio of 3:7), the additive was 5% fluoroethylene carbonate (FEC), and the diaphragm was polypropylene (PP). The positive electrode, negative electrode, electrolyte, and diaphragm were assembled into a simulated battery 4 in an argon-protected glove box.

[0057] Comparative Example 1

[0058] This comparative example provides a method for preparing a battery, which is different from Example 1 mainly in that the preparation of the negative electrode is different, as follows:

[0059] Preparation of negative electrode: Graphite, Super P and carboxymethyl cellulose were slurried in a mass ratio of 8:1:1 with water as solvent and then evenly coated on copper foil and dried at 80°C in vacuum for 12 hours to obtain the electrode Gr.

[0060] Preparation of positive lithium supplement electrode: lithium iron phosphate, Super P, polyvinylidene fluoride (PVDF) are slurried in a mass ratio of 8:1:1 with nitrogen-methylpyrrolidone (NMP) as solvent and evenly coated on aluminum foil and dried in vacuum at 110°C for 12 hours to obtain the pole piece LFP.

[0061] After ammonium molybdate, ammonium tungstate, C3N4 and boric acid were uniformly mixed (the mass ratio of ammonium molybdate to ammonium tungstate was 5:1, the mass volume ratio of C3N4 to boric acid was 5:1, and the mass ratio of ammonium molybdate and ammonium tungstate to C3N4 was 1:2), the mixture was placed in a tubular furnace and heated from 10°C to 800°C for 2 hours to obtain Mo-W@BNC. Subsequently, Mo-W@BNC and a lithium supplement (lithium oxalate: lithium squarate = 1:1) were spray-dried to obtain a composite lithium supplement Mo-W@BNC-L2-L4.

[0062] Mo-W@BNC-L2-L4, KB1400 and PVDF were slurried in a mass ratio of 8:1:1 and homogenized with NMP as solvent, and then evenly coated on LFP as a lithium replenishing layer (the ratio of lithium replenishing layer to LFP was 1:20). After drying, the positive lithium replenishing electrode Mo-W@BNC-L2-L4-LFP was prepared.

[0063] Preparation of simulated battery: Gr was used as the negative electrode of the simulated battery, Mo-W@BNC-L2-L4-LFP was used as the positive electrode, the electrolyte was 1 mol lithium hexafluorophosphate (LiPF6) dissolved in 1L of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (solvent volume ratio of 3:7), the additive was 5% FEC, and the separator was PP. The positive electrode, negative electrode, electrolyte, and separator were assembled into a simulated battery 5 in an argon-protected glove box.

[0064] Comparative Example 2

[0065] This comparative example provides a method for preparing a battery, which is different from Example 1 mainly in that the preparation of the positive electrode is different, as follows:

[0066] Preparation of negative lithium replenishing electrode: Graphite, Super P, and carboxymethyl cellulose were slurried in a mass ratio of 8:1:1 with water as solvent and then evenly coated on copper foil and dried in vacuum at 80°C for 12 hours to obtain the electrode Gr. Gr was then transferred to an inert atmosphere for protection and soaked in 1M lithium biphenyl / tetrahydrofuran solution for 10 minutes, then washed with tetrahydrofuran solvent, and then soaked in FEC-PFPN solvent with a volume ratio of 3:2. After drying, the negative lithium replenishing electrode (p-Gr) was obtained.

[0067] Preparation of positive electrode: lithium iron phosphate, Super P, and polyvinylidene fluoride (PVDF) were slurried in a mass ratio of 8:1:1 using nitrogen-methylpyrrolidone (NMP) as solvent and then evenly coated on aluminum foil and dried at 110°C in vacuum for 12 hours to obtain the electrode LFP.

[0068] Preparation of simulated battery: pGr was used as the negative electrode of the simulated battery, LFP was used as the positive electrode, the electrolyte was 1 mol of lithium hexafluorophosphate (LiPF6) dissolved in 1L of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (solvent volume ratio of 3:7), the additive was 5% FEC, and the separator was PP. The positive electrode, negative electrode, electrolyte, and separator were assembled into a simulated battery 6 in an argon-protected glove box.

[0069] Comparative Example 3

[0070] This comparative example provides a method for preparing a battery, which is different from Example 1 mainly in that the preparation of the positive and negative electrodes is different, as follows:

[0071] Preparation of negative electrode: Graphite, Super P and carboxymethyl cellulose were slurried in a mass ratio of 8:1:1 with water as solvent, and then evenly coated on copper foil and dried at 80°C in vacuum for 12 hours to obtain the electrode Gr.

[0072] Preparation of positive electrode: lithium iron phosphate, Super P, and polyvinylidene fluoride (PVDF) were slurried in a mass ratio of 8:1:1 using nitrogen-methylpyrrolidone (NMP) as solvent and then evenly coated on aluminum foil and dried at 110°C in vacuum for 12 hours to obtain the electrode LFP.

[0073] Preparation of simulated battery: Gr was used as the negative electrode of the simulated battery, LFP was used as the positive electrode, the electrolyte was 1 mol of lithium hexafluorophosphate (LiPF6) dissolved in 1L of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (solvent volume ratio of 3:7), and the additive was 5% FEC. The separator was PP. The positive electrode, negative electrode, electrolyte, and separator were assembled into a simulated battery 7 in an argon-protected glove box.

[0074] Performance Test:

[0075] Electrochemical test steps of simulated batteries: First, simulated batteries 1-4 were charged to 3.7 V at 0.1C (1C=170 mAh / g), and then discharged to 2.5V at 0.1C (1C=170 mAh / g). Subsequently, at a current density of 1C (1C=170 mAh / g), the charge and discharge cut-off voltages were 3.65V and 2.5V, respectively, and the cycle was repeated 1000 times. Subsequently, they were charged to 4.1 V at 0.02C (1C=425 mAh / g), and discharged to 2.5V at 0.02C (1C=425 mAh / g). Subsequently, at a current density of 1C (1C=170 mAh / g), the charge and discharge cut-off voltages were 3.65V and 2.5V, respectively, and the cycle was repeated 2000 times. Then, it was charged to 4.3 V at 0.02C (1C=525 mAh / g) and discharged to 2.5V at 0.02C (1C=525 mAh / g). Then, it was cycled 5000 times at 1C (1C=170 mAh / g) current density with charge and discharge cut-off voltages of 3.65V and 2.5V, respectively. The comparison of the first charge and discharge efficiency and capacity retention rate is shown in Table 1.

[0076] Table 1

[0077]

[0078] As shown in Table 1, when the positive electrode lithium replenishment and the negative electrode lithium replenishment work together, the initial coulombic efficiency and capacity retention rate are both the highest. Negative electrode lithium replenishment is mainly for the initial cycle to ensure the stability of the battery in the early stage of the cycle, while positive electrode lithium replenishment is mainly for the later lithium loss, which can improve the cycle stability after compensation.

[0079] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive and negative electrode coordinated lithium supplement electrode, characterized in that: The negative lithium supplement electrode is a lithium electrode rich in inorganic matter after graphite is pre-lithiated with biphenyl lithium and then treated with fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene. The concentration of biphenyl lithium is 1M, the solvent is tetrahydrofuran, the pre-lithiation time is 5-20 minutes, and the mass ratio of fluoroethylene carbonate and ethoxy (pentafluoro) cyclotriphosphazene is 5-3:2-1. The positive lithium replenishing electrode comprises a positive electrode layer and a lithium replenishing layer coated on the positive electrode layer, wherein the positive electrode layer is a lithium iron phosphate positive electrode layer, and the lithium replenishing layer is a lithium oxalate / lithium squarate composite supported by Mo-W@BNC; wherein the mass ratio of the lithium replenishing layer to the positive electrode layer is 0.5~2:15~20, and the mass ratio of Mo-W@BNC to lithium oxalate / lithium squarate is 0.5~2:5~10; The preparation method of the negative electrode lithium replenishing electrode is as follows: a negative electrode material containing graphite is homogenized and then evenly coated on a copper foil and dried to obtain a pole piece, then the pole piece is transferred to an inert atmosphere for protection and soaked in a lithium biphenyl / tetrahydrofuran solution, then washed with a tetrahydrofuran solvent, then soaked in a fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene solvent, and dried to obtain a negative electrode lithium replenishing electrode; The preparation method of the positive lithium replenishing electrode is as follows: a positive electrode material containing lithium iron phosphate is homogenized and then evenly coated on an aluminum foil and dried to obtain a pole piece; Mo-W@BNC and lithium oxalate and lithium squarate lithium replenishing agents are spray-dried to obtain a composite lithium replenishing agent; a material containing the composite lithium replenishing agent is homogenized and then evenly coated on the pole piece as a lithium replenishing layer, and dried to obtain a positive lithium replenishing electrode; The preparation method of Mo-W@BNC is as follows: ammonium molybdate, ammonium tungstate, C3N4 and boric acid are uniformly mixed and placed in a tubular furnace, heated to 800~900℃ and kept warm for 5~8h to obtain the product; wherein the mass volume ratio of C3N4 to boric acid is 5~3:1~0.5, and the mass volume ratio of ammonium molybdate, ammonium tungstate and C3N4 is 0.5~1:2~4.

2. The positive and negative electrode coordinated lithium supplement electrode according to claim 1, characterized in that: The mass ratio of lithium oxalate to lithium squarate is 0.5~1:1~2.

3. The positive and negative electrode coordinated lithium supplement electrode according to claim 1, characterized in that: In the preparation of the negative lithium-supplemented electrode, the negative electrode material is slurried and coated on the copper foil and then dried at 60~90℃; in the preparation of the positive lithium-supplemented electrode, the positive electrode material is slurried and coated on the aluminum foil and then dried at 100~120℃.

4. The positive and negative electrode coordinated lithium supplement electrode according to claim 1, characterized in that: In the preparation method of Mo-W@BNC, the mass ratio of ammonium molybdate to ammonium tungstate is 5-3:1-0.

5.

5. The positive and negative electrode coordinated lithium supplement electrode according to claim 1, characterized in that: The negative electrode material and the positive electrode material also include a conductive agent and a binder. The content of the conductive agent is 3-5 wt% of the lithium supplement layer material or graphite, and the content of the binder is 3-5 wt% of the lithium supplement layer material or graphite.

6. The positive and negative electrode coordinated lithium supplement electrode according to claim 5, characterized in that: The conductive agent is Super P or KB1400, and the binder is polyvinylidene fluoride or carboxymethyl cellulose or sodium alginate.

7. The positive and negative electrode coordinated lithium supplement electrode according to claim 1, characterized in that: The preparation method of the negative electrode lithium supplement electrode is as follows: graphite, Super P, and carboxymethyl cellulose are homogenized with water as solvent and then evenly coated on copper foil, and vacuum dried at 60-90°C to obtain a pole piece, and then the pole piece is transferred to an inert atmosphere for protection and soaked in a lithium biphenyl / tetrahydrofuran solution for 10 minutes, and then washed with a tetrahydrofuran solvent, and then soaked in a fluoroethylene carbonate-ethoxy (pentafluoro) cyclotriphosphazene solvent, and dried to obtain a negative electrode lithium supplement electrode; The preparation method of the positive lithium replenishing electrode is as follows: lithium iron phosphate, Super P, and polyvinylidene fluoride are slurried with nitrogen-methyl pyrrolidone as a solvent and then evenly coated on an aluminum foil, and vacuum dried at 100-120°C to obtain an electrode piece; Mo-W@BNC and lithium oxalate and lithium squarate lithium replenishing agent are spray-dried to obtain a composite lithium replenishing agent; the composite lithium replenishing agent, KB1400 and PVDF are slurried with nitrogen-methyl pyrrolidone as a solvent and then evenly coated on the electrode piece as a lithium replenishing layer, and dried to obtain a positive lithium replenishing electrode.

8. A battery, characterized in that: A lithium-supplementing electrode comprising the positive and negative electrodes as described in any one of claims 1 to 7.

9. The battery according to claim 8, characterized in that The electrolyte is 1 mol of lithium hexafluorophosphate dissolved in 1 L of a mixed solvent of ethylene carbonate and ethyl methyl carbonate, wherein the volume ratio of ethylene carbonate to ethyl methyl carbonate is 3-5:5-7, the additive is 3-5% FEC, and the separator is PP.

Citation Information

Patent Citations

  • Lithium ion battery and anode strip thereof and stabilization lithium metal powder

    CN102642024A

  • Preparation method and application of lithium supplement material Li5FeO4 for cathode of lithium ion battery

    CN110518297A

  • Preparation method for pre-lithiation of silicon monoxide negative pole piece

    CN112038583A

  • A method for preparing a cathode pre-lithiation material, its product and its application

    CN112542589B

  • Lithium ion battery electrolyte for pre-lithiation of silicon-based negative electrode

    CN114221022A